ZIRCON GEOCHRONOLOGY OF THE SALDA METAMORPHIC COMPLEX, CENTRAL URALS - Krasnobaev A.A.; Davydov V.A. (My University, 2003)
Investigations of zircon geochronology of the Salda metamorphic complex are continued in case of metamorphic rocks in eastern slope of Middle Urals. Results of the investigations make it possible to compare analytic and mineralogical-geochemical parameters of Salda metamorphic complex. Presence of nuclei and substrate fragments entrapped by the growing granulite crystals is base for 2195±68 million year geochronology. Conclusion about opportunity for non-total loss of Salda metamorphic complex memory on early stages of its existence has been made. Data on singleness of zircon formation and rock formation have been obtained. Using the zircon geochronology, similarity of geochronology boundaries of Middle Urals and Southern Urals has been noted.